Comparative Study Between Partially and Fully Recessed‐Gate Enhancement‐Mode AlGaN/GaN MIS HEMT on the Breakdown Mechanism. Issue 16 (30th May 2019) - He, Yunlong; Gao, Hao; Wang, Chong; Zhao, Yaopeng; Lu, Xiaoli; Zhang, Chunfu; Zheng, Xuefeng; Guo, Lixin; Ma, Xiaohua; Hao, Yue
Abstract : In this paper, two enhancement‐mode (E‐mode) AlGaN/GaN recessed‐gate MIS devices with the in situ N2 plasma treatment, known as partially recessed‐gate metal insulator semiconductor (MIS) device and fully recessed‐gate MIS device, are designed. Among them, the partially recessed‐gate MIS device shows excellent characteristics that the threshold voltage of +3.5 V, saturation current density of 722 mA mm −1, peak transconductance of 212 mS mm −1, and the power figure of merit of 4.39 × 10 8  W cm −2 which is the highest value in E‐mode AlGaN/GaN MIS device with the threshold voltage greater than 3 V. Moreover, the current collapse and breakdown voltage of partially recessed‐gate MIS device and fully recessed‐gate MIS device are investigated, and Silvaco simulation is carried out to analyze the difference of breakdown mechanism between two structure devices. Through the analysis of five main breakdown leakage paths, we can get the conclusion that the factor causing the breakdown voltage difference between partially recessed‐gate MIS device and fully recessed‐gate MIS device is the difference in the width of depletion region of the two devices. Abstract : Two enhancement‐mode AlGaN/GaN recessed‐gate MIS devices with the in situ N2 plasma treatment are designed. The partially recessed‐gate metal insulator semiconductor (MIS) device shows excellent characteristics that include the power figure of merit of 4.39 × 10 8  W cm −2, which is the highest value in E‐mode AlGaN/GaN MIS device with the threshold voltage greater than 3 V. Moreover, the breakdown mechanism of partially recessed‐gate MIS device and fully recessed‐gate MIS device are investigated.